Nitrogen and sulfur deposition over a region in SW Europe based on a regional atmospheric chemical transport model. (15th February 2020) - Oliveira, M.A.; Tomlinson, S.J.; Carnell, E.J.; Dore, A.J.; Serrano, H.C.; Vieno, M.; Cordovil, C.M.d.S.; Dragosits, U.; Sutton, M.A.; Branquinho, C.; Pinho, P.
Abstract: Air quality affects both ecosystems and human health. To assess the effects of air pollution, spatially explicit information of pollutants is needed. Atmospheric chemistry transport models are the best option to estimate concentrations and deposition of pollutants, from local to regional scales. However, concentration and deposition maps derived from available regional and global models are typically given at spatial resolutions of 10–50 km and do not contain information at sufficiently high spatial resolution (i.e. ≤ 5 km × 5 km) to identify risks and to develop solutions to protect the ecosystems and human health. Here, we provide deposition and concentration of nitrogen (N) and sulfur (S) at a 5 km × 5 km resolution for the western Iberian Peninsula. The new maps are a major improvement over existing information due to the higher spatial resolution. Comparison with measurements indicates that all maps for N compounds are fit for purpose. Nitrogen deposition in W Iberia ranged from 3 to 38.6 kg N·ha −1 ·year −1, averaging 8.2 kg N·ha −1 ·year −1 with a higher contribution from reduced N forms (62%). Deposition of oxidized forms mainly prevailed in urban and industrial areas and in coastal locations. The contribution of wet deposition was slightly higher (55%) than dry deposition and more important in the North, following the pattern of precipitation. Dry deposition is higher closer to emission sources. Due to their high spatial resolution, these maps can be used for policy development to support ecosystem protection, through the identification of areas at greater risk due to high N deposition. National policy efforts to reduce N pollution must, foremost, target ammonia (NH3 ) emissions in rural areas and oxidized nitrogen (NOx ) emissions in urban and industrialized areas. Highlights: 5 km-grid maps of N & S concentration and deposition were produced for W Iberia. N & S maps were obtained using the FRAME model, most found to be fit for purpose. 62% of N deposition in W Iberia is a contribution from reduced forms. N deposition mostly originates in livestock farming and agricultural activities. At least 14% of the Natura 2000 sites in W Iberia are at risk of eutrophication.